2022
DOI: 10.7554/elife.79957
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell Piezo1 directs the differentiation of TH1 and Treg cells in cancer

Abstract: Dendritic cells (DCs) play an important role in anti-tumor immunity by inducing T cell differentiation. Herein, we found that the DC mechanical sensor Piezo1 stimulated by mechanical stiffness or inflammatory signals directs the reciprocal differentiation of TH1 and regulatory T (Treg) cells in cancer. Genetic deletion of Piezo1 in DCs inhibited the generation of TH1 cells while driving the development of Treg cells in promoting cancer growth in mice. Mechanistically, Piezo1-deficient DCs regulated the secreti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Generally, DCs are resting cells, and once activated they increase the expression levels of surface MHC-peptide complexes and costimulatory molecules, which allows them to efficiently activate T-cells [1]. The immune response induced by DCs is closely related to T-helper type 1 (Th1)/T-helper type 2 (Th2), regulatory T-cells (Tregs)/T-helper type 17 (Th17) [17]. The imbalance of Th1/Th2 and Tregs/Th17 is related to various diseases such as allergies, inflammation, and cancer [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, DCs are resting cells, and once activated they increase the expression levels of surface MHC-peptide complexes and costimulatory molecules, which allows them to efficiently activate T-cells [1]. The immune response induced by DCs is closely related to T-helper type 1 (Th1)/T-helper type 2 (Th2), regulatory T-cells (Tregs)/T-helper type 17 (Th17) [17]. The imbalance of Th1/Th2 and Tregs/Th17 is related to various diseases such as allergies, inflammation, and cancer [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…158 In dendritic cells, PIEZO1 also contributes to mechanical stiffness sensing supporting optimal metabolism and function. 159,160 Pharmacological or shear stress activation of PIEZO1 in vitro also contributes to optimal activation of T cells. 161,162 However, Jairaman et al 163 have shown that deletion of PIEZO1 in T cells does not impact effector CD4 + T-cell response in experimental autoimmune encephalomyelitis, an in vivo murine model of multiple sclerosis, although it attenuates disease severity.…”
Section: Piezo1 Contributes To Immune Cell Functionsmentioning
confidence: 99%
“…PIEZO1 activation also led to a significant increase in the transcription of glycolytic genes, suggesting that PIEZO1 could also play a role in altering DCs metabolic state (Chakraborty et al, 2021). Additionally, mice with DC-specific deficiency of Piezo1 exhibited a moderately decreased anti-tumour response (Chakraborty et al, 2021;Wang et al, 2022), associated with an increase in the differentiation of T reg and decrease in the generation of T H 1 cells (Wang et al, 2022). Furthermore, PIEZO1 can potentiate integrin-mediated mechanosensing and adhesion.…”
Section: Mechanosensitive Ion Channels: Piezo1 and Trpv4mentioning
confidence: 99%